Vascularization of Nanohydroxyapatite/Collagen/Poly(L-lactic acid) Composites by Implanting Intramuscularly In Vivo - Hai Wang; Xiao Chang; Guixing Qiu; Fuzhai Cui; Xisheng Weng; Baozhong Zhang; Xiaojie Lian; Zhihong Wu (International Journal of Polymer Science)
It still remains a major challenge to repair large bone defects in the orthopaedic surgery. In previous studies, a nanohydroxyapatite/collagen/poly(L-lactic acid) (nHAC/PLA) composite, similar to natural bone in both composition and structure, has been prepared. It could repair small sized bone defects, but they were restricted to repair a large defect due to the lack of oxygen and nutrition supply for cell survival without vascularization. The aim of the present study was to investigate whether nHAC/PLA composites could be vascularized in vivo. Composites were implanted intramuscularly in the groins of rabbits for 2, 6, or 10 weeks (n=5×3). After removing, the macroscopic results showed that there were lots of rich blood supply tissues embracing the composites, and the volumes of tissue were increasing as time goes on. In microscopic views, blood vessels and vascular sprouts could be observed, and microvessel density (MVD) of the composites trended to increase over time. It suggested that nHAC/PLA composites could be well vascularized by implanting in vivo. In the future, it would be possible to generate vascular pedicle bone substitutes with nHAC/PLA composites for grafting.